Global Carbon Dioxide Removal Potential of Waste Materials From Metal and Diamond Mining - Bullock, Liam A.; James, Rachael H.; Matter, Juerg; Renforth, Phil; Teagle, Damon A. H. (Frontiers in Climate, 2021)
There is growing urgency for CO2 removal strategies to slow the increase of, and potentially lower, atmospheric CO2 concentrations. Enhanced weathering, whereby the natural reactions between CO2 and silicate minerals that produce dissolved bicarbonate ions are accelerated, has the potential to remove substantial CO2 on decadal to centennial timescales. The global mining industry produces huge volumes of fine wastes that could be utilised as feedstock for enhanced weathering. We have compiled a global database of the enhanced weathering potential of mined metal and diamond commodity tailings from silicate-hosted deposits. Our data indicate that all deposit types, notably mafic and ultramafic rock-hosted operations and high tonnage Cu-hosting deposits, have the potential to capture ~1.1 to 4.5 Gt CO2 annually, between 31 and 125% of the industry’s primary emissions. However, current knowledge suggests that dissolution rates of many minerals are relatively slow, such that only a fraction (~3-21%) of this potential may be realised on timescales of <50 years. Field trials in mine settings are urgently needed and, if this prediction is confirmed, then methodologies for accelerating weathering reactions will need to be developed.